2020
DOI: 10.1111/nph.16518
|View full text |Cite
|
Sign up to set email alerts
|

A lamin‐like protein OsNMCP1 regulates drought resistance and root growth through chromatin accessibility modulation by interacting with a chromatin remodeller OsSWI3C in rice

Abstract: Summary Lamin proteins in animals are implicated in important nuclear functions, including chromatin organization, signalling transduction, gene regulation and cell differentiation. Nuclear Matrix Constituent Proteins (NMCPs) are lamin analogues in plants, but their regulatory functions remain largely unknown. We report that OsNMCP1 is localized at the nuclear periphery in rice (Oryza sativa) and induced by drought stress. OsNMCP1 overexpression resulted in a deeper and thicker root system, and enhanced drou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 89 publications
(110 reference statements)
4
28
0
Order By: Relevance
“…We next examined nuclear localization patterns of MpNMCP proteins by immunohistostaining, in which functional MpNMCP:2HA fusion proteins were visualized with fluorophore-conjugated anti-HA antibodies. As shown by representative images in Figure 3A, MpNMCP is preferentially localized at the nuclear periphery in vivo, which is similar to many NMCP proteins from various plants species (Ciska et al, 2013;Sakamoto and Takagi, 2013;Yang et al, 2020;McKenna et al, 2021). Besides, we found that MpNMCP proteins were not evenly distributed at the nuclear periphery but exhibited a punctate-like pattern, which was similar to that from onion (Ciska et al, 2013).…”
Section: Mpnmcp Is Localized At the Nuclear Periphery But Does Not Control Nuclear Morphologysupporting
confidence: 63%
See 2 more Smart Citations
“…We next examined nuclear localization patterns of MpNMCP proteins by immunohistostaining, in which functional MpNMCP:2HA fusion proteins were visualized with fluorophore-conjugated anti-HA antibodies. As shown by representative images in Figure 3A, MpNMCP is preferentially localized at the nuclear periphery in vivo, which is similar to many NMCP proteins from various plants species (Ciska et al, 2013;Sakamoto and Takagi, 2013;Yang et al, 2020;McKenna et al, 2021). Besides, we found that MpNMCP proteins were not evenly distributed at the nuclear periphery but exhibited a punctate-like pattern, which was similar to that from onion (Ciska et al, 2013).…”
Section: Mpnmcp Is Localized At the Nuclear Periphery But Does Not Control Nuclear Morphologysupporting
confidence: 63%
“…In total, 571 and 472 genes were annotated as up-and downregulated genes shared between two independent mutant lines, respectively (Supplementary Figure 2 and Supplementary Table 1). As the function of NMCP genes in both Arabidopsis and rice has been linked to stress response (Guo et al, 2017;Choi et al, 2019;Jarad et al, 2019;Yang et al, 2020), we postulated that the Mpnmcp mutant transcriptome would show correlation to those stress conditions. To this end, we compared differentially expressed genes (DEGs) in Mpnmcp mutants and several published stress-related Marchantia transcriptomes.…”
Section: Mpnmcp Suppresses Ectopic Onset Of Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis of the mutants, in a line in which topoisomerase initiated homologous recombination was disrupted, suggested that OsSUN1 and OsSUN2 are not completely redundant in function as the Ossun1 single mutant had a normal phenotype but meiosis was disrupted in the Ossun2 mutant. Finally, Yang et al [86] have recently described the interaction between OsNMCP1 and Oriza sativa SWITCH/SUCROSE NONFERMENTING (SWI/SNF) silencing complex. This interaction occurs between OsNMCP1 and OsSWI3C under drought stress conditions leads to the release of OsSWI3C from the SWI/SNF gene silencing complex, thus changing chromatin NUCLEUS accessibility in the genes related to root growth and drought resistance.…”
Section: Cereals Speciesmentioning
confidence: 99%
“…In crops, only rice SNF2 helicase ENDOSPERMLESS 1 (ENL1) has been reported to be involved in syncytial endosperm development, however, as it maintains chromosomal segregation (Hara et al ., 2015). Cereal Snf2 ATPases, such as CHD3/Mi‐2 chromatin‐remodeling factor CHR729/OsCHR4/Rolled Fine Striped (RFS) (Ma et al ., 2015; Cho et al ., 2018), the INO80/SWR ATPase OsINO80 (Li et al ., 2018) and the SMARCAL1 subfamily protein CHR721 (Zhang et al ., 2020) or SWI/SNF accessory component OsSWI3C (Yang et al ., 2020) in rice, as well as ZmCHB101 in maize ( Zea mays ) (Yu et al ., 2016; Yu et al ., 2018; Yu et al ., 2019; Meng et al ., 2020), are involved in vegetative and reproductive development or stress responses. Although the functions of certain chromatin‐remodeling factors have already been identified in rice, little is known about the roles of these and other proteins involved in seed development.…”
Section: Introductionmentioning
confidence: 99%